2022
DOI: 10.3390/d14121078
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Variation Is Driven by Landscape Heterogeneity in an Insular Omnivorous Endemic Lizard, Revealed by DNA Metabarcoding

Abstract: Living on islands entails numerous challenges for animals, among which population density approaching the carrying capacity of trophic resources stands out. To overcome this limitation, many insular lizards can supplement their insectivorous diet with increasing portions of plant material. The Madeira wall lizard, Teira dugesii, is a medium-sized lacertid, endemic to the Madeira and Selvagens archipelagos. As common in this family, adults are sexually dimorphic with males being bigger than females. Previous di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(117 reference statements)
0
2
1
Order By: Relevance
“…Evidence of diet partitioning by age among lizards is widely recorded and juveniles consume a wider range of prey taxa than adults for energy gains (Best and Pfaffenberger, 1987;Chapple, 2003;Rato et al, 2022). In our study no significant intraspecific differences in diet were found between the two age groups.…”
Section: Discussioncontrasting
confidence: 40%
“…Evidence of diet partitioning by age among lizards is widely recorded and juveniles consume a wider range of prey taxa than adults for energy gains (Best and Pfaffenberger, 1987;Chapple, 2003;Rato et al, 2022). In our study no significant intraspecific differences in diet were found between the two age groups.…”
Section: Discussioncontrasting
confidence: 40%
“…Still, in the coming years, the Selvagem Grande population could face potential impacts from the increasing numbers of Madeiran wall lizards after successfully eradicating rabbits and mice. Despite differences in their activity patterns, the generalist diet and behaviour of the wall lizard (Matias et al, 2009;Neves et al, 2017;Neves et al, 2022;Rato et al, 2022), coupled with its greater aggressiveness and larger size, may result in an increase in predation incidents on the eggs, juveniles, and even adult individuals of the Selvagens gecko and competition for food resources and retreat sites (R. Rebelo, pers. obs.…”
Section: Discussionmentioning
confidence: 99%
“…Through intensive sampling efforts, we were able to exceed a target of 20 individuals per population (Rato et al, 2022) for all of our studied populations (Table 1). Lizards were captured across the active season (April-September) to document a summary of total springsummer diet.…”
Section: Field Surveysmentioning
confidence: 99%